Implementacija ukrepa prepovedi približevanja v primeru nasilja nad ženskami na Kosovu - Popovič, Bojan (Socialno delo, 2019)
Author summarizes the development and the implementation of the restraining order in regard to intimate partner violence in Kosovo, where restraining order was first implemented through a UN regulation in 2003. When Kosovo was under UN protectorate and after declaring independence, the Domestic Violence Prevention Act was passed. The enforcement of practically the whole legal framework in Kosovo shows that the international recommendations and standards are carefully followed; however, the enforcement of the restraining order and the inter-institutional cooperation in Kosovo reveal that the measure is not sufficiently imposed. Based on the presentation of the legislative frameworks and the number of restraining orders in Slovenia and Kosovo in 2016, the article summarizes some of the reasons for the (non)implementation, and emphasizes the importance of the (co)operation of institutions, especially the police, center for social work and nongovernmental organizations as crucial actors in case of intimate partner violence. This strengthens the victim's trust in the functioning of the institutions. Author shows the relevance of the transfer of "best practices", from international environment to post-conflict Kosovo, a country which is still a patriarchal environment, diminishing the possibility of implementing an institutional measure.
Keywords: EULEX; kazenski zakonik; Kosovo; nasilje v družini; patriarhalna kultura; policija; zakonodaja; ženske